CURVA CARACTERÍSTICA DO MICROASPERSOR NAANDAN HADAR 7110 - Miola, Ezequiel Cesar Carvalho; Vielmo, Alexandro Luiz; Santos, Karine Lançanova dos; Schons, Ricardo Luis; Robaina, Adroaldo Dias; Peiter, Márcia Xavier (IRRIGA, 2009)
CURVA CARACTERÍSTICA DO MICROASPERSOR NAANDAN HADAR 7110 Ezequiel Cesar Carvalho Miola; Alexandro Luiz Vielmo; Karine Lançanova dos Santos; Ricardo Luis Schons; Adroaldo Dias Robaina; Márcia Xavier Peiter Departamento de Engenharia Rural, Universidade Federal de Santa Maria, RS, ezequielmiola@yahoo.com.br 1 RESUMO Este trabalho foi desenvolvido com o objetivo de determinar alguns parâmetros hidráulicos de um microaspersor NaanDan Hadar 7110 com bocal vermelho de diâmetro 1,10 mm e vazão nominal de 61 l h-1. Conduziram-se testes no Laboratório de Hidráulica Agrícola da Universidade Federal de Santa Maria (UFSM), onde foram determinados a equação característica vazão x pressão e o coeficiente de variação de fabricação (CVf). A equação característica obtida foi , ajustada através de regressão linear, com coeficiente de determinação (r²) de 0,998, caracterizando fluxo turbulento, segundo Pizarro (1990); o coeficiente de variação de fabricação (CVf) médio foi considerado excelente, segundo Solomon (1979), bom, segundo a ABNT (1986) e de categoria A, segundo a ISO 9260 (1991). UNITERMOS: coeficiente de variação de fabricação, relação vazão x pressão, hidráulica. MIOLA, E. C. C.; VIELMO, A. L.; SANTOS, K. L.; SCHONS, R. L.; ROBAINA, A. D.; PEITER, M. X. CHARACTERISTIC CURVE OF THE NAANDAN HADAR 7110 MICROSPRINKLER 2 ABSTRACT This paper was developed with the objective of determining some hydraulic parameters of a microsprinkler NaanDan Hadar 7110 with red mouthpiece of diameter 1,10 mmand nominal flow of 61 lh-1, they behaved tests in the Laboratory of Agricultural Hydraulics of Santa Maria Federal University (UFSM), where they were certain the equation characteristic flow x pressure and the coefficient of production variation (CVf). the obtained characteristic equation was , was adjusted through linear regression, with a coefficient of determination (r²) equal to 0,998, characterizing turbulent flow according to Pizarro (1990); The coefficient of variation of manufacture (CVf ) medium was considered excellent according to Solomon (1979), good according to ABNT (1986) and of category TO according to ISO 9260 (1991). KEY WORDS: manufacturing variation coeffient, flow x pressure relationship, hydraulic.